Segmental Analysis of Employees’ Performance Reviewed from Transformational Leadership and Job Satisfaction (Empirical Study on Study Program Staff at Health Polytechnic, Tanjung Karang Lampung) - Gunarso, Sri Indra Tri; Moeins, Anoesyirwan (International Review of Management and Marketing, 2019)
This study aims to determine and analyze the relationship between transformational leadership and job satisfaction with the performance of study program employees in Tanjungkarang Health Polytechnic, Lampung Province. The population of this study was 291 persons or the entire employees, while the sampling was using slovin formula so a number of 168 employees were obtained. Collecting data technique was using questionnaire instrument while data analysis tool was using statistic of simple linear regression and Correlation Coef. Based on the results of quantitative analysis using Correlation Coef, it was found that transformational leadership and job satisfaction variables are closely related to the performance of study program employees at Tanjungkarang Health Polytechnic partially or simultaneously. These results illustrate that employees’ performance with acceptance of criticism as indicators that are highly determined by satisfaction is assessed through increased job performance and job satisfaction as well as transformational leadership in particular the leaders’ directives for employees in understanding the organizational vision and mission. As for the partial Correlation Coef of each r=0.457 and Determinant Coef of R2=0.324. This study recommends that employees’ performance at Ministry of Health’s Tanjungkarang Health Polytechnic can be improved through efforts to improve job satisfaction at employees’ job performance by offering awards and paying attention to career improvement for excelling employees, additionally this can be achieved by improving employees’ understanding of organizational vision and mission through leaders’ directives in transformational leadership. Keywords: Transformational Leadership, Job Satisfaction, and Employee Performance. JEL Classifications: M12, M54, N75 DOI: https://doi.org/10.32479/irmm.7448